Micro-structured inverted pyramid texturization of Si inspired by self-assembled Cu nanoparticles. Issue 2 (21st December 2016) - Wang, Yan; Liu, Yaoping; Yang, Lixia; Chen, Wei; Du, Xiaolong; Kuznetsov, Andrej
Abstract : A systematic demonstration of the mechanism of Cu nanoparticle assisted chemical etching for inverted pyramid texture both theoretically and experimentally. Abstract : A superior micron-sized inverted pyramid structure has been successfully achieved by one-step copper nanoparticles assisted chemical etching in Si/Cu(NO3 )2 /HF/H2 O2 solution for light trapping in silicon solar cells. The detailed mechanisms of such a novel method have been systematically demonstrated. The charge transfer during the reaction has been revealed by the simplified energy band diagram of the system as well. In order to form micro-structured inverted pyramids, the generation and dissolution of Cu nanoparticles should keep in balance during the reaction, which depends on the concentration of the etchant, the doping type and the doping level of the silicon substrate. With the investigation of the intrinsic properties of the silicon substrate, the etching rate is found out as a combined result of the electron concentration and the defect density of the substrate, as well as the potential barrier on the interface of Si/Cu nanoparticles. Furthermore, the anisotropic nature of Cu assisted chemical etching has also been investigated.